Transformation ratio at interaction of long sequence of electron bunches with plasma - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2011)
The efficiency of wakefield excitation in plasma by sequence of electron bunches is determined by transformation ratio. Using code LCODE, the 2d3v-numerical simulation has been performed and transformation ratio has been investigated for long train of electron bunches. The cases of shift of bunches on phases relative to excited wave, shaping of densities of bunches in nonlinear regime and combined case have been considered, which lead to values of transformation ratio, essentially exciding the limiting value 2. Ефективність збудження кільватерного поля в плазмі послідовністю електронних згустків визначається коефіцієнтом трансформації. Використовуючи код LCODE, проведено 2d3v-числове моделювання і досліджено коефіцієнт трансформації для довгої послідовності електронних згустків. Розглянуті випадки зміщення згустків по фазі відносно збуджуваної хвилі, профілювання густини згустків у нелінійному режимі і комбінований випадок, які приводять до величин коефіцієнту трансформації, значно перевищуючих значення 2. Эффективность возбуждения кильватерного поля в плазме последовательностью электронных сгустков определяется коэффициентом трансформации. Используя код LCODE, проведено 2d3v- численное моделирование и исследован коэффициент трансформации для длинной последовательности электронных сгустков. Рассмотрены случаи смещения сгустков по фазе относительно возбуждаемой волны, профилирования плотности сгустков в нелинейном режиме и комбинированный случай, которые приводят к величинам коэффициента трансформации, существенно превышающим предельное значение 2.